Analysis of excursion activities of UNESCO World Heritage Site (on the example of the Residence of the Metropolitans of Bukovina and Dalmatia) - Zayachuk, Oksana; Krul, Halyna (Modern scientific research: achievements, innovations and development prospects. Proceedings of the 11th International scientific and practical conference. MDPC Publishing. Berlin, Germany, 2022)
The role of the architectural ensemble is defined of the former Residence of the Metropolitans of Bukovyna and Dalmatia in the sightseeing tourism and analyzed excursion activities on the territory of the research object after its inclusion in the UNESCO World Heritage List.
Keywords: excursion activities; UNESCO World Heritage site; The Residence of the Metropolitans of Bukovina and Dalmatia; historical and architectural sites